The Influence of Student Financial Literacy on Actual Users Digital Wallet - Eldon, Mokhamad (International Conference On Economics Business Management And Accounting (ICOEMA), 2024)
In the era of digitalization, Industrial Revolution 4.0, and society 4.0, many conveniences can be made in various aspects of life, including using digital wallets. Indonesia, as a developing country, is the number one country contributing the most traffic to the Shopee e-commerce site. This research aims to determine the influence of three financial literacy components on the financial satisfaction of digital wallet users in e-commerce. The research subjects are students belonging to Generation Z. The three components of financial literacy consist of financial behavior, financial attitude and understanding of financial knowledge. This research uses a quantitative descriptive analysis method, with a purposive sampling method to determine the population consisting of Tulungagung University students who own ShopeePay Indonesia accounts. The sample data used was 259 ShopeePay Indonesia account holders. Data collection techniques used literature studies and questionnaires with Likert scale techniques. The analysis technique in this research uses multiple linear regression analysis with SPSS 24 software tools. The results of the research show that the variables financial behavior (X1), financial attitude (X2) and financial knowledge (X3) partially influence financial satisfaction significantly. The financial behavior, financial attitude and financial knowledge variables simultaneously influence the financial satisfaction of Shopeepay digital wallet users among students. Thus, there needs to be development in this research and it can be used as theoretical support, especially in the financial literacy component.